Caplacizumab use in immune-mediated thrombotic thrombocytopenic purpura: an international multicentre retrospective Cohort study (The Capla 1000+ project)Research in context - Paul Coppo; Michael Bubenheim; Ygal Benhamou; Linus Völker; Paul Brinkkötter; Lucas Kühne; Paul Knöbl; Maria Eva Mingot-Castellano; Cristina Pascual-Izquierdo; Javier de la Rubia; Julio del Rio Garma; Shruti Chaturvedi; et al. (EClinicalMedicine)
Summary: Background: The anti-Von Willebrand Factor (VWF) nanobody caplacizumab is licensed for adults with immune-mediated thrombotic thrombocytopenic purpura (iTTP) in association with therapeutic plasma exchange (TPE) and immunosuppression. However, whether caplacizumab reduces mortality, and its optimal timing of initiation, is not completely settled. Methods: This international, multicenter retrospective cohort study recruited patients from 2018 until 2023 and data collection took place from January 1st to June 30th 2023 in the participating centers. One thousand and fifteen patients were treated with daily TPE, immunosuppression with corticosteroids ± rituximab, and caplacizumab (caplacizumab group), which was compared to historic controls treated with TPE and corticosteroids ± rituximab (control group, N = 510). Caplacizumab initiation was classified as early (within 3 days; 76% of cases) or delayed (≥4 days from first TPE). Findings: Three-month survival rate in the caplacizumab group was 98.5%, compared with 94% in controls (P < 0.0001). Three-month mortality rate was 4.2-fold higher in controls than in caplacizumab-treated patients (95% CI: 2.22–7.7, P < 0.0001), regardless of rituximab use. In both groups, death was observed primarily in elderly patients, and age was the factor most associated with 3-month mortality. Patients receiving caplacizumab showed reduced refractoriness, exacerbations, and required fewer TPE sessions to achieve clinical response versus controls (P < 0.0001 all). Time to clinical response in the caplacizumab group was shorter than in controls, and even shorter in patients with early caplacizumab initiation (P < 0.0001 both). Caplacizumab-related adverse events were observed in 21% of patients, with major bleeding in 2.4%, which was more common in elderly patients. Interpretation: The early association of Caplacizumab to TPE and immunosuppression significantly reduces unfavorable outcomes during iTTP, including death, and alleviates the burden of care at the potential expense of bleeding events. Advanced age, however, remains an adverse factor for survival. The limitations of our study include its retrospective and multicentric design and the use of a historical control cohort. Funding: None.